B.B. Mitra on the code of criminal procedure, 1973, act 2 of 1974, vol.1 - Roy, S. R.; Mitra, B. B., -1935.; India (Calcutta : Kamal Law House, 1991)
Revised and updated with latest court decisions; includes text of the 1973 Act.
Includes index.
Keywords: Criminal procedure -- India